The Development of Interactive English Multimedia in Tourism Vocational Education as an Adaptive Learning Strategy in the Midst of Covid-19 Pandemic - Dwi Novita Cahyaningtyas Permatasari; Luh Mega Safitri (Unit Pelayanan Bahasa, Politeknik Pariwisata Bali, 2022)
The online learning process on tourism vocational education during COVID-19 pandemic has been observed to be nonoptimal in Indonesia. Lack of educators’ knowledge and skills in creating interactive media was the obstacle, where at vocational education, more practice was required rather than theoretical materials delivery. The idea of “digital for everything” was introduced as the standard phase of work. This world has forced by Covid-19 pandemic to the digitalization. This study has two objectives, first to identify barriers in learning process, and second, to develop interactive English multimedia. This research was designed as R&D method. The research subjects involved media and contents experts as alpha test subjects. Alpha test results were used as the basis for the first revision. Participation of PIB students with high, medium, and low abilities were used as beta test subjects. The final product was validated by the validator team, then applied in the learning process. The results showed there was an increase in student satisfaction from moderate (5.81) to very good (8.21) when lecturers apply interactive multimedia using videos, animations and other interactive multimedia. Developed interactive English for tourism multimedia was effective during COVID-19 pandemic and can be accessed by students anywhere and anytime.